Parallel patterns determination in solving cyclic flow shop problem with setups - Bożejko, Wojciech; Chaczko, Zenon; Uchroński, Mariusz; Wodecki, Mieczysław (Archives of Control Sciences, 2017)
Abstract The subject of this work is the new idea of blocks for the cyclic flow shop problem with setup times, using multiple patterns with different sizes determined for each machine constituting optimal schedule of cities for the traveling salesman problem (TSP). We propose to take advantage of the Intel Xeon Phi parallel computing environment during so-called ’blocks’ determination basing on patterns, in effect significantly improving the quality of obtained results.